Antecedents and Consequences of Technostress among Employees in Digital Work Environments: A Systematic Literature Review - Puspita Sari; Verica Sofie Putibungsu; Retno Dwiyanti; Ugung Dwi Ario Wibowo (The Future of Education Journal, 2026)
The rapid advancement of digital transformation has increased organizations' reliance on technology to support daily work activities. While digital technologies enhance operational efficiency and productivity, they also expose employees to digital work-related stress, commonly referred to as technostress. This study aims to identify the factors influencing technostress among employees in digital organizations using a Systematic Literature Review (SLR) approach. Relevant articles were retrieved from the Scopus database using the search query TITLE-ABS-KEY ("technostress" AND employee). Article selection followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, applying predefined inclusion and exclusion criteria, which resulted in 11 eligible studies for analysis. The findings indicate that technostress is influenced by three major categories of factors: technological, organizational, and individual factors. Technological factors emerged as the most influential, particularly techno-overload, digital workload, constant connectivity, and digital surveillance. Organizational factors, including organizational support, organizational culture, and digital leadership, were also found to significantly affect employees' levels of technostress. Meanwhile, individual characteristics such as self-efficacy, resilience, and technological adaptability play a critical role in helping employees cope with digital work-related stress. Furthermore, the review demonstrates that technostress has significant implications for employee well-being, work–life balance, work exhaustion, and job performance within digital work environments.